Synthesis and Characterization of 2- and 4-Substitued Pyridine Carbothionamides and 2- and 4-Pyridinethio Carbonyl Ureas - Ramachandran, K.L. (Asian Journal of Chemistry, 2016)
The four compounds, viz., 2- and 4-N-(n-butyl)pyridine carbothionamides as well as 2- and 4-pyridine thiocabonyl ureas were synthesized using 2- and 4-pyridine carbonitrile with n-butylamine and urea in the ratio 1 : 4 respectively in the presence of H2S. The prepared compounds were characterized using IR, NMR and mass spectra and the structures were determined.